Genome-shock deletion of a hybrid lethality gene breaks a reproductive barrier and facilitates speciation in Nicotiana - Nagai, Shota; Kawaguchi, Kenji; Itakura, Hiroki; Matsumoto, Kaho; Iizuka, Takahiro; Kobayashi, Kosaku; Nakata, Kouki; Yamada, Tetsuya; Marubashi, Wataru; Yanase, Masanori; Morikawa, Toshinobu; Yokoi, Shuji; et al. (Frontiers in Plant Science, 2025)
Allopolyploidization plays an important role in the evolution of eukaryotes. Allopolyploids formed through interspecific hybridization and polyploidization undergo genetic and epigenetic changes in the early generations, known as ‘genome shock’. However, reproductive isolation often prevents interspecific hybridization. The mechanism by which a reproductively isolated species breaks reproductive barriers and crosses with other species is largely unknown, despite its importance in speciation and evolution. Here, we report the ultrahigh-frequency appearance of viable hybrids that overcame hybrid lethality, a type of reproductive isolation, in crosses between Nicotiana tabacum and N. amplexicaulis. Lethal hybrids exhibited Type II hybrid lethality characterized by browning of hypocotyl and roots at 28 °C, temperature sensitivity, and involvement of the Q chromosome from N. tabacum genome, indicating that N. amplexicaulis possesses the causal allele for hybrid lethality at the Hybrid Lethality A1 (HLA1) locus. Random amplified polymorphic DNA, amplified fragment length polymorphism, and methylation-sensitive amplified polymorphism analyses have detected genetic and epigenetic changes in viable and lethal hybrids, suggesting the occurrence of genome shock during interspecific hybridization. We found that many viable hybrids exhibited HLA1 locus deletion, indicating that it was the primary cause of overcoming hybrid lethality in these crosses. These findings demonstrate that genome shock-induced genetic changes promote the breakdown of reproductive barriers through the deletion of causal genes, providing insights into the mechanisms by which reproductively isolated species can overcome barriers and lead to the formation of new species.